Work Environment More Determinant of Performance in the Food Logistics Industry: Lingkungan Kerja Lebih Berpengaruh terhadap Kinerja di Industri Logistik Pangan - Putri Inul Budiastuti; Sumainah Fauziah (Universitas Muhammadiyah Sidoarjo, 2025)
General Background: In the context of globalization and digital transformation, employee performance has become a critical determinant of organizational effectiveness, particularly in the food logistics sector that supports national food security. Specific Background: At BULOG Subdivre Surabaya Utara, challenges related to employee motivation, remuneration fairness, and adaptation to a changing work environment indicate the need for evidence-based human resource management strategies. Knowledge Gap: Although prior studies have examined compensation and work environment separately, limited empirical research has simultaneously analyzed their relative and combined effects on employee performance within public food logistics organizations. Aims: This study aims to analyze the influence of salary and work environment on employee performance at BULOG Subdivre Surabaya Utara. Results: Using a quantitative approach and multiple linear regression analysis of survey data, the findings reveal that both salary and work environment have positive and statistically significant effects on employee performance, with the work environment showing a stronger contribution. Novelty: This study provides sector-specific empirical evidence highlighting the dominant role of non-financial factors alongside compensation in a strategic public logistics institution. Implications: The findings imply that management should balance fair remuneration systems with continuous improvements in physical and psychosocial work conditions to sustainably improve employee performance and organizational outcomes. Highlights: The work environment plays a more dominant role than salary in shaping employee performance. Fair compensation remains essential to sustain motivation and productivity. Integrated human resource strategies are crucial for performance improvement in public food logistics organizations. Keywords: Salary, Work Environment, Employee Performance, Food Logistics, Human Resource Management